Czech Monetary Policy in the Face of Inflation Extremes - Zeman, Mikuláš (2025)
The main objective of this dissertation thesis is to assess the effectiveness of the Czech National Bank’s (CNB) monetary policy actions. Effectiveness is primarily evaluated based on the ability to deliver the CNB’s key mandate, which is price stability. The assessment focuses on the CNB’s responses to two specific and crucial economic situations: (i) the low inflation period accompanied by the zero lower bound in 2013 and (ii) the post-Covid inflation surge in 2022. The dissertation thesis applies advanced econometric methods for this assessment, specifically the Granger causality test and vector autoregressive (VAR) models. The key findings are as follows: (i) the unconventional monetary instrument in the form of the exchange rate commitment, adopted in response to the low-inflationary environment in 2013, entailed more drawbacks than benefits, which the CNB had to address long afterwards, and (ii) the CNB’s response to the inflation surge in 2022 was both effective and appropriate. The dissertation also presents Granger causality tests and VAR models applied to selected macroeconomic variables of the euro area. On average, the CNB's monetary policy appears to have been more effective and responsive than that of the ECB in the two situations analyzed. In addition, this dissertation thesis confirms the validity of real business cycle theory by means of an extended real business cycle (RBC) model from the class of DSGE models that incorporates capital utilization. The results indicate that policymakers have limited ability to smooth economic fluctuations caused by supply shocks and that too active monetary management is often not desirable due to its inflationary consequences.